Hopf bifurcation in an open monetary economic system: Taylor versus inflation targeting rules - Mohseni, Reza Moosavi; Kilicman, Adem (Elsevier, 2014)
The main aim of the present work is to detect the Hopf bifurcation in policy relevant economic dynamical system. The study employs two deferent forms of monetary policy rules namely: Taylor rule and inflation targeting rule. The results show that there exists Hopf bifurcation between policy relevant variables in both types of rules in our open economic system.